Answer:
(x + 1)² = 7
Step-by-step explanation:
Given:
-2x = x² - 6
We'll start by rearranging it to solve for zero:
x² + 2x - 6 = 0
The first term is already a perfect square so that's fine. Normally, if that term had a non-square coefficient, you would need to multiply all terms a value that would change that constant to a perfect square.
Because it's already square (1), we can simply move to the next step, separating the -6 into a value that can be doubled to give us the 2, the coefficient of the second term. That value will of course be 1, giving us:
x² + 2x + 1 - 1 - 6 = 0
Now can group our perfect square on the left and our constants on the right:
x² + 2x + 1 - 7= 0
x² + 2x + 1 = 7
(x + 1)² = 7
To check our answer, we can solve for x:
x + 1 = ± √7
x = -1 ± √7
x ≈ 1.65, -3.65
Let's try one of those in the original equation:
-2x = x² - 6
-2(1.65) = 1.65² - 6
- 3.3 = 2.72 - 6
-3.3 = -3.28
Good. Given our rounding that difference of 2/100 is acceptable, so the answer is correct.
Answer:
Get a calculator
Step-by-step explanation:
Most of the time for simple math like multiplying 2 digits, it is easiest if you just get a calculator. It saves a lot of time.
If you can't get a calculator then i recommend memorizing some common equations.
For example 10*15= 150
so that if you get 12*15=?, you can easily just add two extra 15's to your answer of 150.
15+15 is 30, and 30+150(from 10*15)=180.
Therefore 12*15=180.
:) Hope that helped!
Answer:
-114
Step-by-step explanation:
It’s blank is the answer lol we can’t see it
I would start by plugging in a number for x. Just any random number. Let's take 2 for example. Then the equation would go from 2x + y = -4, to 2(2) + y = -4. Then solve.
2(2) + y = -4
4 + y = -4, after you've done that, plug in a number for y, that completes the equation. In this case, the only acceptable number, would be -8. Because it completes the number sentence.
4 + (-8) = -4
-4 = -4.
Now plug in other numbers, to get the same outcome. Hope this helped!
-Twixx